2020
DOI: 10.1136/oemed-2019-106353
|View full text |Cite
|
Sign up to set email alerts
|

Preventing sickness absence among employees with common mental disorders or stress-related symptoms at work: a cluster randomised controlled trial of a problem-solving-based intervention conducted by the Occupational Health Services

Abstract: ObjectivesCommon mental disorders (CMDs) are among the main causes of sickness absence and can lead to suffering and high costs for individuals, employers and the society. The occupational health service (OHS) can offer work-directed interventions to support employers and employees. The aim of this study was to evaluate the effect on sickness absence and health of a work-directed intervention given by the OHS to employees with CMDs or stress-related symptoms.MethodsRandomisation was conducted at the OHS consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Figure 1 shows the recruitment of consultants, intervention and control groups ( Figure 1 is copied without changes from Keus van de Poll et al [ 8 ] under a CC BY 4.0 license). Randomization took place at the OHS consultant level using computer-generated random numbers randomizing OHS consultants into giving either PSI or CAU.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 shows the recruitment of consultants, intervention and control groups ( Figure 1 is copied without changes from Keus van de Poll et al [ 8 ] under a CC BY 4.0 license). Randomization took place at the OHS consultant level using computer-generated random numbers randomizing OHS consultants into giving either PSI or CAU.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approval was obtained from the Ethical Review Board in Stockholm (registration number 2015/549-31/1). More details of the study design and procedures have been reported elsewhere [ 8 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations